Beginning AutoCAD 2012 exercise workboook - Shrock, Cheryl R. (Industrial Press, 2011)
Totally updated for AutoCAD 2012 and 2012 LT, this workbook includes 30 lessons with step-by-step instructions followed by exercised designed for practicing the commands learned within the lesson. Providing only what you need without all of the jargon, it is ideal for classroom instruction or as a self-study tutorial.